Walking backwards into the future: Prophecy as an approach for embedding Indigenous values in tertiary education - Rangiwai, Byron (Te Kaharoa, 2021)
Indigenous peoples understand time differently to Pākehā (Rangiwai, 2021a). Mahuika (2010) maintains that the notion of walking backwards into the future is a common one for Māori and other people of the Pacific. Roberts (2005) opines, “It is often said that Māori are a people who “walk backwards into the future,” an aphorism that highlights the importance of seeking to understand the present and make informed decisions about the future through reference to the past” (p. 8).